Role of Ecuadorian Women in Scientific Writing. Case Study: Central University of Ecuador - Morejón-Caiza, Gladys (2021)
Today women have a considerable place in science, however, this was not always the case, as ancient ideologies sowed the idea that women can contribute to science. The research was carried out with the objective of making visible the degree of female participation in the writing of scientific articles. For this, an analysis was developed on the evolution of the scientific production of fourth-level teachers. The contributions of the authors of scientific articles corresponding to three main areas were compared: Life and Health Sciences, Exact Sciences and Social Sciences in the periods between the 2014 - 2018 and 2016-2018. The data was taken from the Portal of Journals of the Central University of Ecuador (UCE), until the first semester of 2019. The work was carried out in the city of Quito, Pichincha province. The quantitative methodology was applied: data counting was carried out, which were used in the statistical analysis to establish the differences of authors and authors. As outstanding results, it was found that the largest number of articles was produced in 2017, both internally and externally, with 58.3% corresponding to the authors and 41.6% belonging to the authors, which highlights 16.7% of difference in scientific writing distributed in each of the areas defined above.